Development in a Time of Global Interdependence - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, spoke about the complex and vexing challenges which the world faces today. He explained how the major issues that evolve in a developing country now swiftly move to affect developed countries. He discussed three points to tackle at the global level. First, address the challenge of global threats that cross boundaries and regions will become ever more central to achieving the mission to end extreme poverty. Second, focus much more effectively on managing risk and uncertainty. Third, much more must be done to address the deep pockets of poverty and rising inequality in countries at every income level.